Triphenyl phosphate promotes lipid accumulation in human mesenchymal stem cells through metabolic stress pathways - M. C. Gronske; W. Stutts; D. Jima; J. Palumbo; H. M. Stapleton; S. W. Kullman (Archives of Toxicology, 2026)
Organophosphate esters (OPEs), used as both plasticizers and flame retardants, are increasingly recognized for their potential to disrupt cellular homeostasis and emerging evidence indicates their ability to induce metabolic stress in diverse biological systems. This study investigated the impact of Triphenyl Phosphate (TPhP) on human mesenchymal stem cell (hMSC) differentiation and cell stress. hMSCs were treated with DMSO (vehicle control), 10 µM rosiglitazone (a PPARγ agonist), or 25 µM TPhP for 14–21 days. Following treatment, cells were stained to assess nuclear integrity, lipid accumulation, and mineralization. Immunocytochemistry (ICC) for osteogenic and adipogenic markers was used to determine whether TPhP promotes adipogenesis under osteogenic conditions. TPhP exposure led to significant lipid accumulation without activation of adipogenic differentiation programs and markedly reduced mineralization. In particular, co-treatment with PPARγ inhibitors did not mitigate lipid accumulation or modulate the expression of adipogenic regulators. Gene expression analysis following TPhP exposures revealed upregulation of pathways involved in lipid biogenesis, triglyceride synthesis, phospholipid metabolism and endoplasmic reticulum (ER) stress, with minimal changes to classical adipogenic markers. These findings indicate that TPhP disrupts the metabolic balance between osteogenesis and lipid metabolism, with the potential to promote ectopic lipid deposition within the bone forming environment. This dysregulation is relevant for the development of metabolic disorders, including obesity, type 2 diabetes, and metabolic bone diseases, including osteoporosis.

Habitat fidelity in hawksbill sea turtles - Andrew S. Maurer; Julia A. Horrocks; Claudio Bellini; Karen L. Eckert; Alexandra L. Fireman; Mariana M. P. B. Fuentes; Barry Krueger; Kathryn E. Levasseur; Maria A. Marcovaldi; Renata M. A. Ramos; Seth P. Stapleton; Hannah B. Vander Zanden; et al. (Ecology, 2025)
Climate change is altering habitat suitability and driving shifts in species distributions. To understand potential responses by mobile animals, it is essential to assess levels of plasticity in habitat use, ranging from transience to long‐term fidelity. Here, we evaluate the fidelity of hawksbill sea turtles ( Eretmochelys imbricata ) to habitats used while foraging (our primary focus), migrating, and nesting. After satellite tracking 17 adult females from three Western Atlantic nesting areas, we then re‐tracked them in a subsequent year. Of 15 turtles with sufficient data to assess interannual foraging area fidelity, 14 returned to the same home range, exhibiting overlap between successive 50% utilization distributions (UDs); the 15th individual shifted

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Children’s exposure to chemical contaminants: Demographic disparities and associations with the developing basal ganglia - Carina H. Fowler; Aaron Reuben; Heather M. Stapleton; Kate Hoffman; Nicholas Herkert; Lubna Barakat; Michael S. Gaffrey (Environmental Research, 2024)

Associations of environmental chemical exposures measured in personal silicone wristbands with sociodemographic factors, COVID-19 restrictions, and child respiratory health - Brennan H. Baker; Drew B. Day; Marnie F. Hazlehurst; Nicholas J. Herkert; Heather M. Stapleton; Sheela Sathyanarayana (Environmental Research, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

PFAS levels in paired drinking water and serum samples collected from an exposed community in Central North Carolina - Samantha M. Hall; Sharon Zhang; George H. Tait; Kate Hoffman; David N. Collier; Jane A. Hoppin; Heather M. Stapleton (Science of The Total Environment, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Polybrominated Diphenyl Ethers in American Eels (Anguilla rostrata) from the Delaware River, USA - J. T. F. Ashley; D. Libero; E. Halscheid; L. Zaoudeh; H. M. Stapleton (Bulletin of Environmental Contamination and Toxicology, 2007)

The fate of 15 N added to high Arctic tundra to mimic increased inputs of atmospheric nitrogen released from a melting snowpack - A. M. Tye; S. D. Young; N. M. J. Crout; H. M. West; L. M. Stapleton; P. R. Poulton; J. Laybourn‐Parry (Global Change Biology, 2005)
Increases in the long‐range aerial transport of reactive N species from low to high latitudes will lead to increased accumulation in the Arctic snowpack, followed by release during the early summer thaw. We followed the release of simulated snowpack N, and its subsequent fate over three growing seasons, on two contrasting high Arctic tundra types on Spitsbergen (79°N). Applications of 15 N (99 atom%) at 0.1 and 0.5 g N m −2 were made immediately after snowmelt in 2001 as either Na 15 NO 3 or 15 NH 4 Cl. These applications are approximately 1 × and 5 × the yearly atmospheric deposition rates. The vegetation at the principal experimental site was dominated by bryophytes and Salix polaris while at the second site, vegetation included bryophytes, graminoids and lichens. Audits of the applied 15 N were undertaken, over two or three growing seasons, by determining the amounts of labeled N in the soil (0–3 and 3–10 cm), soil microbial biomass and different vegetation fractions. Initial partitioning of the 15 N at the first sampling time showed that ∼60% of the applied 15 N was recovered in soil, litter and plants, regardless of N form or application rate, indicating that rapid immobilization into organic forms had occurred at both sites. Substantial incorporation of the 15 N was found in the microbial biomass in the humus layer and in the bryophyte and lichen fractions. After initial partitioning there appeared to be little change in the total 15 N recovered over the following two or three seasons in each of the sampled fractions, indicating highly conservative N retention. The most obvious transfer of 15 N, following assimilation, was from the microbial biomass into stable forms of humus, with an apparent half‐life of just over 1 year. At the principal site the microbial biomass and vascular plants were found to immobilize the greatest proportion of 15 N compared with their total N concentration. In the more diverse tundra of the second site, lichen species and graminoids competed effectively for 15 NH 4 ‐N and 15 NO 3 ‐N, respectively. Results suggest that Arctic tundra habitats have a considerable capacity to immobilize additional inorganic N released from the snow pack. However, with 40% of the applied 15 N apparently lost there is potential for N enrichment in the surrounding fjordal systems during the spring thaw.

Comparing Polybrominated Diphenyl Ether and Polychlorinated Biphenyl Bioaccumulation in a Food Web in Grand Traverse Bay, Lake Michigan - H. M. Stapleton; J. E. Baker (Archives of Environmental Contamination and Toxicology, 2003)

Sedimentary Nonylphenol Contamination in an Urbanized, Industrialized Segment of the Delaware River Estuary, USA - J. T. F. Ashley; A. Moore; H. M. Stapleton; D. J. Velinsky; M. P. Wilhelm (Bulletin of Environmental Contamination and Toxicology, 2003)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)